Finding Winnie : the true story of the world's most famous bear - Mattick, Lindsay; Blackall, Sophie (2015)
A woman tells her young son the true story of how his great-great-grandfather, Captain Harry Colebourn, rescued and learned to love a bear cub in 1914 as he was on his way to take care of soldiers' horses during World War I, and the bear became the inspiration for A.A. Milne's Winnie-the-Pooh.
Keywords: Colebourn, Harry, -- 1887-1947 -- Juvenile fiction; Colebourn, Harry, -- 1887-1947 -- Fiction; Winnie-the-Pooh -- (Fictitious character) -- Fiction; Milne, A. A. -- 1882-1956 -- Fiction; Winnipeg (Bear) -- Juvenile fiction; Winnipeg (Bear) -- Fiction; Bears -- Fiction; Soldiers -- Fiction